Developing Channel Strategy to Increase Sales; Case Study: Perangkat Industri (PT Jokulin Indonesia Mandiri) - Yulius, Mayang Dita Anggryany; Rudito, Priyantono (The Indonesian Journal of Business Administration, 2013)
This research describes the distribution channel strategy is suitable for Perangkat Industri, which is one area of business of PT Jokulin Indonesia Mandiri. Perangkat Industri is an ecommerce business in the industrial field. As a new player in the industry, Perangkat Industri has several internal and external issues that have an impact on the future of the company. The main problem faced by Perangkat Industri is the distribution channel for marketing products to customers. In solving the problem, there are several alternatives that can be used by Perangkat Industri, which is channel distribution through the distribution channel websites, distributors, and salesperson. Three distribution channels are analyzed based on the existing distribution channels (existing channel) and channels based on customer requirements (ideal channel). From the analysis of the resulting channel strategies, that is to make improvements and take advantage of the existing distribution of channels and based on customer requirements, the distribution channels through the website, distributors, and salesperson. The strategy then becomes a recommendation to the company for use as a reference to develop and survive in competition with competitors of this business.Â Keywords: Industry, Ecommerce, Perangkat Industri, Channel Strategy, Distribution Channel